Análise da associação dos marcadores cagT, LEC e oipA funcional e não funcional do Helicobacter pylori em afecções gástricas - Gonçalves, Maria Helane Rocha Batista (2015)
The Helicobacter pylori is a bacterium that colonizes the gastric mucosa of human beings. The chronic infection caused by this pathogen is strongly associated with an increased risk for gastric illnesses different, ranging from chronic gastritis and peptic ulcer for two types of gastric cancer, adenocarcinoma and lymphoma of the lymphoid tissue associated to mucosa. The aim of this study was to evaluate the association of cagT markers, LEC, functional and nonfunctional oipA in patients with disorders of gastritis, ulcers and stomach cancer. Genotyping of the strains was performed by PCR. Were evaluated 181 patients attended at the University Hospital Walter Cantídio, 87 (48.1%) men, 94 (51.9%) women, with ages ranging from 18-90 years, mean age of 53 + 17.8 years, with a positive diagnosis for H. pylori infection, these 48 carriers of gastric cancer, 69 patients with peptic ulcer and 64 with gastritis. The prevalence of the genotypes studied was: 145/181 (80.1%) cagT, 83/181 (45.9%) LEC 81/181 (44.7%) oipA and oipA"on"34/81.In the group of patients with gastric cancer was observed that the most frequent genotype was the cagT 43/48 (89,5%), followed by the oipA gene "on" 10/18 (55.6%) and LEC 17/48 (35.4%). In the group of patients with peptic ulcer genotype was the most frequent cagT 62/69 (89.8%), followed by gene LEC, 34/69 (49.3%) and the oipA"on" 13/31 (41.9%). In the group of patients with the most frequent genotype gastritis was cagT 40/64 (62.5%), followed by gene LEC 32/64 (50.0%) and the oipA "on" 11/32 (34.4%). Furthermore, by the presented data there is no association of H. pylori and gender and or age of the patients.The genetic study of the markers of H. pylori infection and its relationship with the gastric disorders is essential to establish the profile of virulence of strains and thus elucidate the clinical outcomes variables involved with this infection.